Prospect of Cattle Development to Support Self Sufficiency of Meat in North Sumatera Province - Akhmad Rifai Lubis (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2010)
Shortage of beef supply to meet national needs is also found locally in North Sumatera Province. The trend  for beef in this area was triggered by the increasing of population, economic improvement and  desire for better nutrient comsumption. Level of beef consumption is increased 17% from year 2004 to 2008, so in the same period the number of cattle entered into the North Sumatera Province also increased. Some efforts had been conducted to develop beef cattle program in North Sumatera Self Sufficiency Program in Beef through technical and policy approaches. Several programs have been developed to accelerate the development of productivity and the population in North Sumatra, among others, 1) Agribusiness Development Program, 2) Food Security Improvement Program, 3) Farmer's Welfare Program; which are financed by both central and local budgets. Institutional aspects that have been developed to support the PSDS-2014 is the Regional Artificial Insemination Center to serve the needs of semen for districts and municipalities in the Province of North Sumatera. In the year 2008, it has been distributed as many as 44 000 doses of semen for frozen semen to meet the demands of 11 Districts. The amount of land resources for development indicated the availability of pastural land area of 1,311,159 ha from oil palm and rubber plantation, area of 1,192,172 ha for crops and livestock integration system. It is estimated that biomass production of rice straw, bean straw and sugarcane straw reaches 7,062,227; 68 145 and 14 664 tons per year, respectively. Also available as many as 689,478 tons of rice bran and palm oil industry waste as much as 4,159,203 tons per year. Some challenges in the North Sumatera PSDS programs in accordance with a predetermined time include: 1) Not all of the stakeholders get a complete information about the program, 2) the difficulties to prevent productive cows being slaughtered, 3) limited capital in an effort to pick up and redistribute productive cows before slaughtered, 4) small scale ownership of cattle thus slowing the adoption of technological innovations. Key words: Cattle, self-sufficiency, North Sumatera